Die Walze und die Geige - Tarkovskij, Andrej Arsen'evic; Jusov, Vadim Ivanovic; Fomcenko, Igor'; Zamanskij, Vladimir Petrovic; Adzhubei, Marina (trigon-film blu-ray-edition, 2014)
At the center of the film is the unlikely friendship between Sasha, a young boy who loves to play the violin, and Sergey, he macho driver of a steamroller. The film sidesteps sentimentally to give us a warm yet ironic look at two individuals who bridge differences in generations to form a powerful bond. Available for the first time, The Steamroller and the Violin features a brilliantly natural performance from the young Igor Fomchenko, in a film that is memorable and deeply affecting- a re-discovered gem that strikes close to the heart. [Facets Video]